2010
DOI: 10.1038/ijo.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

A microarray analysis of sexual dimorphism of adipose tissues in high-fat-diet-induced obese mice

Abstract: Objective A sexual dimorphism exists in body fat distribution; females deposit relatively more fat in subcutaneous/inguinal depots whereas males deposit more fat in the intra-abdominal/gonadal depot. Our objective was to systematically document depot- and sex-related differences in the accumulation of adipose tissue and gene expression, comparing differentially expressed genes in diet-induced obese mice with mice maintained on a chow diet. Research Design and Methods We used a microarray approach to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
175
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(199 citation statements)
references
References 49 publications
21
175
1
2
Order By: Relevance
“…We verified the hypothesis (see Introduction) that the capacity for enlargement is increased in adipocytes of female compared with male mice in response to a long-term HF feeding, possibly reflecting the higher insulin sensitivity of the female adipocytes. In contrast to similar studies performed previously, 6,7,19 the sex-dependent metabolic phenotypes observed in this mouse model of dietary obesity could not be attributed to a lower body weight gain, adiposity and/or smaller fat cells in females. Most of the results were confirmed by an independent experiment on a separate cohort of animals (not shown).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…We verified the hypothesis (see Introduction) that the capacity for enlargement is increased in adipocytes of female compared with male mice in response to a long-term HF feeding, possibly reflecting the higher insulin sensitivity of the female adipocytes. In contrast to similar studies performed previously, 6,7,19 the sex-dependent metabolic phenotypes observed in this mouse model of dietary obesity could not be attributed to a lower body weight gain, adiposity and/or smaller fat cells in females. Most of the results were confirmed by an independent experiment on a separate cohort of animals (not shown).…”
Section: Discussioncontrasting
confidence: 99%
“…Most of the results were confirmed by an independent experiment on a separate cohort of animals (not shown). Study of Grove et al, 19 published recently in this journal, showed less inflamed gWAT in female than in male C57BL/6 mice fed HF diet for 12 weeks after weaning, with female mice having lower fat mass. Moreover, in female mice, the size of adipocytes tended to be smaller in gWAT, whereas it was significantly smaller in scWAT.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations